PERANAN BADAN PENGAWAS PEMILIHAN UMUM DALAM PEMILIHAN UMUM LEGISLATIF KABUPATEN KUANTAN SINGINGI TAHUN 2019 - Fajri Aristides; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The role of the general election supervisory body in the general election is an activity of observing, assessing and assessing the process of holding elections in accordance with statutory regulations. Has the authority to prevent violations in the election and also to supervise the election. The research approach is qualitative with descriptive analysis method by describing phenomena and data accurately. The research location is BAWASLU, Kuantan Singingi Regency. Sources of research data are primary data and secondary data. Data collection techniques used by interview and documentation. The results of this study are the role of the General Elections Supervisory Board in supervising the implementation of the 2019 Kuantan Singingi Regency Legislative Elections that have not been carried out to the maximum, this can be proven from the results of research that supervision has not been carried out in accordance with the laws and regulations, namely supervision of updating voter data, establishing lists temporary voters and permanent voter lists, supervision of the implementation of campaigns and campaign funds and supervision of election logistics procurement and distribution. However, Bawaslu has carried out well, namely the supervision of nominations related to the requirements and procedures for nomination of members of the legislature and the determination of candidates for legislative members. Keywords: Role, Supervision and General Election